Regulation of miRNAs in obesity and diabetes - Eva Maher; Ava O'Meara; Cathy Brougham (SURE Journal: (Science Undergraduate Research Experience Journal))
Introduction: The prevalence of obesity and obesity-related secondary disorders has increased dramatically in recent years. Dysregulated microRNA (miRNA) expression has been linked to the development of obesity and its associated disorders. Adipose derived stem cells (ADSCs) are promising cell models of obesity, obesity-related inflammation and diabetes. Furthermore, miRNA expression profiles have emerged as promising targets for the novel treatment of diseases such as obesity. In order to enhance miRNA-based therapies, the miRNA expression profile of obesity and its related disorders must be monitored to further understand the underlying mechanisms of obesity and to identify novel targets. Aim: The aim of this study was to identify the expression profile of six target miRNAs and three target cytokines. The expression of these targets was compared to control ADSCs, ADSCs differentiated into adipocytes and ADSCs from diabetic patients using a series of tissue culture, molecular biology, and biochemical techniques. This study compares these findings with available literature to identify miRNAs and cytokines that could be novel targets in obesity and diabetes-based therapeutic approaches. Results: The expression of miR-A, miR-221, miR-222, miR-21, miR-146 and miR-133 were significantly dysregulated in obese and diabetic patients compared to controls. MiR-A, a novel miRNA, was identified in this study and was significantly increased in diabetes compared to control samples. Transforming Growth Factor-beta (TGF-β), Tumour Necrosis Factor-alpha (TNF-α) and Vascular Endothelial Growth Factor A (VEGFA) were differentially expressed across each of the cell cohorts investigated. Conclusion: This study identified a novel miRNA and revealed that significant changes in miRNA and cytokine expression have the potential to identify obese patients from diabetic patients. The identification of dysregulated miRNAs and in particular novel dysregulated miRNAs, may lead to the development of miRNA-based personalised therapeutics for obesity and diabetes.